Ethiopia Poverty Assessment : Harnessing Continued Growth for Accelerated Poverty Reduction - World Bank (World Bank, Washington, DC, 2020)
This poverty assessment focuses on the evolution of poverty and other social indicators in Ethiopia between 2010-11 and 2015-2016 (henceforth referred to as 2011 and 2016). Using data from a variety of sources, mainly the twinned household living standards surveys (HCES and WMS), the Ethiopia Socioeconomic Survey (ESS) and the Demographic and Health Surveys (DHS), the poverty assessment documents trends in monetary and non-monetary dimensions of living standards and examines the drivers of observed trends, with a special focus on government programs. The aim of the poverty assessment is to provide policy makers and development partners with information and analysis that can be used to improve the effectiveness of their poverty reduction and social programs.